7(x+3)-7=22-3x-8+10x

Simple and best practice solution for 7(x+3)-7=22-3x-8+10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+3)-7=22-3x-8+10x equation:


Simplifying
7(x + 3) + -7 = 22 + -3x + -8 + 10x

Reorder the terms:
7(3 + x) + -7 = 22 + -3x + -8 + 10x
(3 * 7 + x * 7) + -7 = 22 + -3x + -8 + 10x
(21 + 7x) + -7 = 22 + -3x + -8 + 10x

Reorder the terms:
21 + -7 + 7x = 22 + -3x + -8 + 10x

Combine like terms: 21 + -7 = 14
14 + 7x = 22 + -3x + -8 + 10x

Reorder the terms:
14 + 7x = 22 + -8 + -3x + 10x

Combine like terms: 22 + -8 = 14
14 + 7x = 14 + -3x + 10x

Combine like terms: -3x + 10x = 7x
14 + 7x = 14 + 7x

Add '-14' to each side of the equation.
14 + -14 + 7x = 14 + -14 + 7x

Combine like terms: 14 + -14 = 0
0 + 7x = 14 + -14 + 7x
7x = 14 + -14 + 7x

Combine like terms: 14 + -14 = 0
7x = 0 + 7x
7x = 7x

Add '-7x' to each side of the equation.
7x + -7x = 7x + -7x

Combine like terms: 7x + -7x = 0
0 = 7x + -7x

Combine like terms: 7x + -7x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 85=1-x | | 0.02=0.8(y+0.1) | | -7c=41/5 | | 1/5X+2=15 | | -6+8(x-2)=15x+6-7x | | 9+7y=-21 | | 2(x-3)+5x=5+7(x+3) | | 1=-8+2x | | -9=2v-3 | | 6x-(2x-3)=4x+5 | | x^4+4x^3+12x^2+12x-9=0 | | X/3+6=11 | | -5s=-1.25 | | 13x+19y=-17 | | 6x+75=9x+93 | | -2+8(x-5)=13x+6-5x | | -3(y-0.5)=0.5 | | -8.978=1.34t | | 3x(2-4)=24 | | -0.67(x+1)=6 | | 4(a-5)+6=2(a-6) | | 8x-3=7(x+5)+4 | | -5s=1.25 | | 3/4x-1=7/5 | | 9x-2=6x+43 | | -3=5(z+7) | | 3X+8Y=30 | | 24=-8y | | 4x^2-19x+24=-2x+9 | | 4x^2-16x+24=-2x+9 | | 12(r-2)=0 | | (8r-64)/4 |

Equations solver categories